Case Series: Risk and Clinical Manifestation of Non-Convulsive Status Epilepticus After Traumatic Brain Injury - Ramli, Yetty (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Traumatic brain injury occurs due to impacts on the head or penetrating injuries that result in damage to the brain. Traumatic brain injury can lead to complications, including post-traumatic seizures. Seizures following traumatic brain injury (TBI) present a complex interplay of various risk factors and determinants that significantly impact clinical outcomes and patient management, especially in non-convulsive status epilepticus. Non-convulsive status epilepticus (NCSE) is an underrecognized complication following traumatic brain injury (TBI), with potentially severe consequences for patient outcomes. Factors contributing to NCSE development include level of consciousness, injury severity, and cortical involvement. Clinical presentation is often subtle, ranging from altered mental status to focal neurological deficits. Early recognition through EEG monitoring is crucial, guiding targeted antiepileptic therapy to mitigate neuronal injury and improve outcomes Understanding these risk factors and clinical manifestations are crucial for effective surveillance, early intervention, and tailored treatment strategies aimed at mitigating the burden of seizures and improving the long-term prognosis of individuals with TBI.